ETIKA PROFESI ADVOKAT SEBAGAI UPAYA PENGAWASAN DALAM MENJALANKAN FUNGSI ADVOKAT SEBAGAI PENEGAK HUKUM - Pramono, Agus (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2016)
Indonesia as a state of law based on Pancasila and the Constitution of the Republic of Indonesia Year 1945 guarantees equality for all before the law (equality before the law). In realizing the principles of law in the society and state, the role and function of Advocate as a profession that is free, independent and responsible is important, in addition to the judiciary and law enforcement agencies such as the police and prosecution. The problems in this dissertation are: (1) What are the basic ratiologic advocate violation of professional ethics Advocate? and (2) How does the concept of behavioral guidelines advocate in practicing a profession as legal counsel in an effort to control the Advocate in law enforcement? The method used is normative research enables researchers to utilize the findings of empirical legal science and other sciences for the benefit and the analysis and explanation of law without changing the character of law as a normative science. The method used in this research is the approach of legislation or statute approach, arguing that research must necessarily normative approach legislation, because examined are various rules of law as well as its central theme a focus of research. The results of basic research advocate consideration as a respectable profession and became an important part of chess dynasty law enforcement, Advocate has responsibility in undertaking to participate in the realization of the rule of law. The responsibility is not merely a necessity but a legally mandated obligations arising from the demands of conscience. The obligations of an advocate is reflected in the ability of responsible advocate against God, professional code of ethics, rules of law and society. Ultimately lawyer also required to be able to account for his actions to the public as an implementation of a sense of responsibility to God, codes and regulations. The concept of behavioral guidelines advocate in practicing a profession as a lawyer as Advocate control efforts in law enforcement by law or code of ethics which is already adequate, but rather on how to implement them. Relating to the existence of a single container and how to manage the Honorary Council (DK) Organization. Monitoring system needs to be upgraded with the supervision of the Advocate smoothed by the Advocate Organization with the Honorary Council to enforce the Law on Advocates and the Code of Conduct.